SIPPING ENTERAL NUTRITION: CLINICAL – PHARMACOLOGICAL ANALYSIS AND OPPORTUNITIES OF ITS USE IN THE INTENSIVE CARE - I. E. Khoroshilov (Вестник анестезиологии и реаниматологии)
The article presents the results of comparative analysis of the 13 mixtures for sipping (oral) enteral feeding, most commonly used in RF, which are prescribed during the transfer from tube feeding to regular diet, and also when it is impossible to take regular food, in case of hypercatabolism (in traumas, burns, severe sepsis), anorexia nervosa, cachexy. The special emphasis is put onto the inexpediency of enteral tube administration of highly osmolar sipping mixtures if there is risk of osmotic diarrhea.